PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK) DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN - Karnila Ali; Nur Wahyu Ningsih (Universitas Muhammadiyah Metro Lampung, 2021)
This study aims to determine the Effect of Original Revenue, General Allocation Funds, Special Allocation Funds and Economic Growth on Unemployment in the Metro City Government Period 2013-2018. This type of research is quantitative in the form of secondary data. Secondary data was conducted at the Statistics Central Agency (BPS), the Regional Financial and Asset Management Agency (BPKAD), the Social Service (DINSOS), the Manpower and Transmigration Office and the Regional Tax and Retribution Management Agency (BPPRD) in the Metro City Government. The data analysis model used in this study uses multiple regression analysis. The results of this study indicate that the Original Income, General Allocation Fund, Special Allocation Fund and Economic Growth have no effect on unemployment. So that in budgeting the allocation and has not been maximized to manage and optimize sectors related to Economic Growth and reduce the unemployment rate.Keywords: Local Revenue, General Allocation Fund, Special Allocation Fund, Economic Growth and Unemployment